2016
DOI: 10.1016/j.jcrs.2016.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different types of phacoemulsification tips. I. Quantitative analysis of elemental composition and tip surface microroughness

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This difference in depth analysis can explain the different chemical elements detected by XPS and EDS. Tsaousis et al 9,10 obtained similar results, ascribing the difference in elemental composition to the difference in the depth of analysis between EDS and XPS. The main outcome of XPS analysis in the present study was the detection of a superficial silicon layer of the surface of used tips compared with new tips.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This difference in depth analysis can explain the different chemical elements detected by XPS and EDS. Tsaousis et al 9,10 obtained similar results, ascribing the difference in elemental composition to the difference in the depth of analysis between EDS and XPS. The main outcome of XPS analysis in the present study was the detection of a superficial silicon layer of the surface of used tips compared with new tips.…”
Section: Discussionmentioning
confidence: 72%
“…The surface average roughness doubled in value, indicating extreme deterioration of the tip. In part I of their study, Tsaousis et al 9 compared the profilometry of 7 new phaco tip models, concluding that the results might be affected by defective areas of phaco tips. The authors added that a smooth tip surface could be gentler to ocular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drills used in the implant surgeries are extensively used in dental applications (Porto, et al, 2015;Allsobrook, et al, 2011). Some manufacturers suggest that the life span of the drills is approximately ten surgical procedures (Allsobrook, et al, 2011;Chacon, et al, 2006;Tsaousis, et al, 2016). To ensure safe treatment and to prevent cross-contamination, an efficient sterilization process is necessary (Porto, et al, 2015;Allsobrook, et al, 2011;Fais, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we found studies employing alloy 420B in milling cutters for dental implants. As some manufacturers have suggested that the life of implant cutters is approximately 10 surgical procedures (Allsobrook, et al, 2011;Chacon, et al, 2006;Tsaousis, et al, 2016), in the present study, 20 sterilization cycles were performed to simulate multiple use and analyze the consequent microstructural and electrochemical changes.…”
mentioning
confidence: 99%